Seen, Heard, and Still Missing: Understanding Clinical Trial Nonparticipation Among Women of Color - Jasmine Dionne Souers; Marissa Thomas; Juliette Faughnan; Mary Fox; Nishtha Gupta; Gail Betz; Adishree Nayak; Nathaniel Laban; Christabel K. Cheung (Journal of Adolescent and Young Adult Oncology, 2026)
Purpose: To examine structural, informational, and cultural barriers to clinical trial participation among women of color (WOC), with emphasis on adolescents and young adults (AYAs), through a community-partnered study to illuminate persistent challenges and generate actionable strategies through community-driven research. Methods: In partnership with For the Breast of Us , a national advocacy organization for WOC affected by breast cancer, we conducted a sequential exploratory mixed-methods study. In-depth interviews ( n = 59) informed a national online survey ( n = 421) assessing trial perceptions, knowledge, and participation among WOC across the United States, both with and without a breast cancer diagnosis, the majority of whom were AYAs. Results: Five themes emerged distrust and historical harms; logistical and structural barriers; cultural relevance and representation; fear and silence; and access to health care and information. Quantitatively, WOC were less likely than White women to have discussed trials with a provider (36% vs. 58%, p < 0.05), to know how to enroll (64% vs. 41%, p < 0.01), and to perceive trials as “not for people like me” (79% vs. 47%, p < 0.01). Age-stratified analyses further showed that women ages 19–30 reported lower clinical trial knowledge and greater informational, trust-related, and practical barriers than older participants. Conclusion: Barriers to trial participation are structurally embedded and racially patterned, with age-stratified findings suggesting distinct informational, trust-related, and practical barriers among younger women. Transforming who clinical trials are for begins by transforming how they are built.